2013
DOI: 10.1371/journal.pone.0081705
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Replacement in Current Aquaculture Feed: Is Cholesterol a Hidden Treasure for Fish Nutrition?

Abstract: Teleost fish, as with all vertebrates, are capable of synthesizing cholesterol and as such have no dietary requirement for it. Thus, limited research has addressed the potential effects of dietary cholesterol in fish, even if fish meal and fish oil are increasingly replaced by vegetable alternatives in modern aquafeeds, resulting in progressively reduced dietary cholesterol content. The objective of this study was to determine if dietary cholesterol fortification in a vegetable oil-based diet can manifest any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 45 publications
2
44
0
4
Order By: Relevance
“…Nitrogen free extract (NFE) was calculated by difference, and energy was computed on the basis of 23.6, 39.5 and 17.2 kJ/g of protein, fat and carbohydrate, respectively. Fatty acids were separated, identified and quantified using gas chromatography, following procedures previously described in detail (Norambuena et al, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen free extract (NFE) was calculated by difference, and energy was computed on the basis of 23.6, 39.5 and 17.2 kJ/g of protein, fat and carbohydrate, respectively. Fatty acids were separated, identified and quantified using gas chromatography, following procedures previously described in detail (Norambuena et al, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…However, this happens at a significant metabolic cost (18 acetyl‐CoA, 18 ATP, 16 NADPH, and 4 O 2 molecules per molecule of cholesterol), and it has been suggested that aquafeeds not providing sufficient quantities of cholesterol (e.g., plant‐based formulations) should be fortified with additional cholesterol to improve overall fish performance (Norambuena et al. ). Accordingly, cholesterol is garnering additional interest from fish nutritionists (Leaver et al.…”
Section: Lessons Learned From Nutrient‐based Research In Fish Oil Spamentioning
confidence: 99%
“…Lipid content was determined by dichloromethane:methanol extraction (2:1) technique (Folch et al, 1957), with the substitution of chloroform with dichloromethane for safety reasons and the addition of butylated hydroxytoluene (BHT) (50 mg L − 1 ) to reduce lipid oxidation during processing. After lipid extraction, an aliquot was used for fatty acid analysis, which was implemented via trans-methylation and gas chromatography, following the procedures previously described in detail (Norambuena et al, 2013b).…”
Section: Performance Parameters and Chemical Analysesmentioning
confidence: 99%